Ensuring Rights: Improving Access to Sexual and Reproductive Health Services for Female International Students in Australia - Poljski, Carolyn; Quiazon, Regina; Tran, Chau (Journal of International Students, 2014)
Drawing on the research and advocacy work being conducted by the Multicultural Centre for Women’s Health (MCWH), a national community-based organization in Victoria, Australia, the paper analyzes female international students’ experiences with accessing sexual and reproductive health information and services. Accessibility of sexual and reproductive health services is one of a number of areas identified by MCWH in which international students experience unequal treatment. The limitations of international students’ mandatory health insurance is of particular concern because it appears to conflict with Australia’s human rights obligations to take all appropriate measures to eliminate discrimination and to ensure appropriate services in connection with pregnancy. Given the social, cultural and economic benefits international students bring to the country in which they choose to study, state action on equitable health access for international students is urgently called for.